2020
DOI: 10.1177/0892705720930737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple extrusions on structure–property relationships of hybrid wood flour/poly (vinyl chloride) composites

Abstract: This study emphasizes on closed-loop recycling of wood flour/poly (vinyl chloride) composites, since there is normally a considerable amount of material waste in wood plastic production lines. Composite materials were produced and subjected to four times reprocessing cycles under industrial conditions. Detailed analytical methods including bending strength, modulus of elasticity, impact strength, scanning electron microscopy, fiber length, water absorption, contact angle, Fourier transform infrared, and dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The reason behind the reduction of EMC after 2 months of fungal attack can be attributed to the fact that the studied white-rot fungus degrades lignin (hydrophobic) to a higher extent in the incipient stage of decay vs. cellulose. As the decay proceeds in the following months, the fungus also degrades cellulose besides lignin; this probably leads to the reduced EMC values in longer fungal exposure times (4 months), since there is less hydrophilic cellulose content to keep water (Das et al 2000; Hosseini and Naghdi 2004; Ashori et al 2013; Yousefi et al 2017; Bahmani et al 2018; Nadali and Naghdi 2020). Statistical analysis indicated that there was a significant difference between the equilibrium moisture content (EMC) of WPC and MDF specimens after 2 and also 4 months of exposure to T. versicolor .…”
Section: Resultsmentioning
confidence: 99%
“…The reason behind the reduction of EMC after 2 months of fungal attack can be attributed to the fact that the studied white-rot fungus degrades lignin (hydrophobic) to a higher extent in the incipient stage of decay vs. cellulose. As the decay proceeds in the following months, the fungus also degrades cellulose besides lignin; this probably leads to the reduced EMC values in longer fungal exposure times (4 months), since there is less hydrophilic cellulose content to keep water (Das et al 2000; Hosseini and Naghdi 2004; Ashori et al 2013; Yousefi et al 2017; Bahmani et al 2018; Nadali and Naghdi 2020). Statistical analysis indicated that there was a significant difference between the equilibrium moisture content (EMC) of WPC and MDF specimens after 2 and also 4 months of exposure to T. versicolor .…”
Section: Resultsmentioning
confidence: 99%
“…Different mechanisms can play a role in this regard, briefed as follows: (1) The silicate layers of the studied nanoparticles expand the tortuous path, thus delaying the diffusion of degraded volatile compounds throughout the composites due to their high aspect ratio as well as formation of intercalation structure, 101 (2) A char layer is formed on the external surfaces of composite materials by nanoclay/silica; this leads to the insulation of the sub layer, therby preventing the nanocomposite from burning and the resulting higher degradation temperatures and better thermal stability, 25 (3) Strong interaction between the nanoclay silicate layers and polypropylene chains can limit chain mobility. This delays the process of conveying free radicals formed in the course of polymer fragmentation brought about by thermal degradation and enhances the thermal stability of nanocomposites, 98,102 (4). Rigid and impervious nanoclay layers may decrease heat conduction; thus, their presence in nanocomposite formulations not only limits the mobility of polymer chains but also inherently improves composites thermal performance, 103 (5) The pores created by the crystalline structure of OMMT act as some thermal insulation sites leading to enhanced thermal performance.…”
Section: Tgamentioning
confidence: 99%
“…[1][2][3] These inexpensive wastes not only hold a large share of municipal wastes across the globe but also are suitable for WPC production due to their low melting and processing temperature being below the degradation temperature of natural fibers (<200°C). 4 Agricultural wastes (wheat straw, rice hull, bagasse, coir, etc.) have recently gained much attention as a potential alternative for wood in the production of different lignocellulosic products due to their abundance, accessibility, low price, and acceptable properties (vs. wood).…”
Section: Introductionmentioning
confidence: 99%
“…These inexpensive wastes not only hold a large share of municipal wastes across the globe but also are suitable for WPC production due to their low melting and processing temperature being below the degradation temperature of natural fibers (<200°C). 3,4 Water absorption is a major drawback in wide application of WPCs which is affected by the kind and amount of WPC constituents. The hydrophilic nature of natural fibers introduces phenomenal problems in WPCs which are poor interfacial adhesion of the given fibers with the hydrophobic plastic matrix as well as providing a proper condition for fungal attack.…”
Section: Introductionmentioning
confidence: 99%